Pandemic-activated psychological growth: significance of extraversion, self-consciousness and COVID-19 related anxiety - Magdalena Żurko; Aleksandra Słowińska; Alicja Senejko; Kamila Madeja-Bień; Zbigniew Łoś (Current Issues in Personality Psychology, 2022)
Background The sense of threat to health and life in the face of a pandemic, accompanied by difficulties imposed by lockdown, may trigger a serious crisis. Among possible consequences of such a crisis may paradoxically be the phenomenon of psychological growth. The aim of this article is to identify predictors of pandemic-activated psychological growth (PPG). The relationships between extraversion, reflective and ruminative self-consciousness and PPG were the subject of our inquiry. Additionally, a question was posed about the indirect effect of self-consciousness on PPG through anxiety.